Reduction of the clastogenic effect of inorganic arsenic by extracts of some dietary additives (2004)
The clastogenic effects of aqueous' extracts of Garlic (Allium sativum.L) (Ga), African pepper (Xylopia aethiopica) (Ap), Bush pepper (Piper guincense) (Bp) and African nutmeg (Monodora myristica). (An) at 100mg/kg body weight each administered orally either alone and in combination with a single oral dose of sodium arsenite (2.5mg/kg body wciglit, 1/10th, of LD50) were investigated in mouse bone marrow cells. The results obtained show that Ga induced micronucleus formation in the polychromatic erytrocytcs (PCEs) of the bone marrow by about 12 folds followed by Bp (7 folds), Ap (4 folds) and An (1 fold) in comparison with animals exposed to distilled water only. These results indicate that Ga, Bp and Ap have mild clastogenic activity in micc. ln contrast, sodium arsenite, a known clastogen, induced micronuclcatcd PCEs formation by about 90 folds. Interestingly treatment of mice with extracts of the dietary additives Ga, Bp, Ap and An, markedly reduced the clastogenic activity of sodium arsenite in the order Ap > Ga > An > Bp. Maximum reduction of arsenite eftcct was about 60% with Bp. it may be concluded therefore from these findings that garlic, African pepper, bush pepper and African nutmeg may be useful in dietary manipulation of arsenic intoxications.